1993
DOI: 10.1016/0014-5793(93)81382-a
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin induced cAMP and IP3 responses in PC12 cells

Abstract: NGF and BDNF elevate cAMP and IP3 levels in membranes of PC12 cells within a subsecond time period. The cAM P formation induced by NGF and BDNF pretreatment for 2 s was reduced by GDP‐β‐S and PTX, but not the trkNGFR inhibitor K 252a. NGF, but not BDNF, induced IP3 formation. IP3 formation was reduced by K 252a, but not by GDP‐β‐S and PTX. Using p75NGFR expressing, but trkNGFR‐deficient PCNA cell membranes, NGF and BDNF induced cAMP formation, but not IP3 formation. We suggest that NGF and BDNF induced cAMP fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…Second, NGF is shown for the first time to signal directly through the second messenger cAMP via adenylyl cyclase activation. It was previously reported that NGF can elevate cAMP levels within 1 s in the membranes of PC12 cells (6). These investigators proposed cross-talk between the low affinity neurotrophin receptor p75 NTR and a G protein-mediated cascade.…”
Section: Discussionmentioning
confidence: 94%
“…Second, NGF is shown for the first time to signal directly through the second messenger cAMP via adenylyl cyclase activation. It was previously reported that NGF can elevate cAMP levels within 1 s in the membranes of PC12 cells (6). These investigators proposed cross-talk between the low affinity neurotrophin receptor p75 NTR and a G protein-mediated cascade.…”
Section: Discussionmentioning
confidence: 94%
“…In PC12 cells deficient in PKA, treatment with NGF increased the levels of both mRNA and saxitoxin binding for type II sodium channels; however, recordings showed no detectable I Na in these cells, indicating that PKA was critical in the expression of functional channels (Ginty et al 1992). Although early studies demonstrated that NGF rapidly increased intracellular levels of cyclic AMP (Higuchi et al 2003;Knipper et al 1993), establishing a causal link has been elusive. Recent studies in PC12 cells showed that NGF elevated cyclic AMP levels through activation of soluble rather than transmembrane adenylyl cyclase and that this cyclic AMP increased the activity of the small G protein, Rap1 (Stressin et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma cells contain nerve growth factor (23) and high affinity nerve growth factor receptor, Trk A, is expressed in small and medium diameter DRG neurons (24), which also express ET A receptor (18). Nerve growth factor elevates cAMP (25) and cAMP up-regulates ET A -receptor mRNA (26). Thus, nerve growth factor might be a cause of the increase in ET A -receptor mRNA in the DRG of melanoma-bearing mice.…”
Section: Discussionmentioning
confidence: 99%